ML-18 Clinical diagnosis for suspected primary central nervous system lymphoma patients without histopathological confirmation - Osawa, Sho (Neurooncol Adv, 2020)
Background: The gold standard of the diagnosis of primary central nervous system lymphoma (PCNSL) is the histopathological diagnosis by biopsy surgery. However, we experience some cases with a high risk of biopsy surgery or difficulty in general anesthesia. We perform radiation and chemotherapy without histopathological confirmation for such patients based on imaging findings, ophthalmological evaluation, and cerebrospinal fluid examinations. In this study, we investigated clinical diagnosis and outcomes for patients suspected PCNSL. Method: From April 2016 to December 2019, all adult brain tumor patients that were diagnosed with PCNSL without histopathological confirmation and underwent radiation and/or chemotherapy were included. The following criteria were retrospectively analyzed. 1) Intraorbital lymphoma, 2) SUV(max)>12 in (18)F FDG-PET, 3) ADC(mean)<0.98×10(–3) mm(2)/s in MRI diffusion-weighted images, 4) tumor to normal ratio >1 in late phase of (123)I IMP SPECT, 5) CSF β2 microglobulin >2.1 mg/l, 6) CSF sIL2R >77 U/ml, 7) Improvement of imaging findings or clinical symptoms by steroid. Result: 9 suspected PCNSL patients were included. 8 patients were positive for 3 or more above criteria. All these patients achieved CR by initial treatment with radiation or chemotherapy which indicated appropriate diagnosis for PCNSL. The remaining 1 patient was SD by radiotherapy, which was an atypical clinical course of PCNSL. The above criteria were positive in 2 and negative in 3. There were no examinations that could be performed in all cases before the treatment. Conclusion: Some useful markers for the diagnosis of PCNSL have been reported. However, all have limited sensitivity and specificity. Each examinations are also restricted by patient, institution and time. The combination of the useful examinations will improve the diagnostic accuracy of PCNSL.